IMPLEMENTASI KEBIJAKAN PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) DI KANTOR PERTANAHAN NASIONAL KABUPATEN TABANAN - Ameita Raydila, Ni Desak Made; Yasintha, Putu Nomy; Wirantari, I Dewa Ayu Putri (CITIZEN CHARTER, 2019)
ABSTRACT The purposemof thismresearch is to find out the Implementation ofcPTSLnPolicy at NationalmLandmOffice of Tabanan Regency. This researchcused a qualitativenmethod with a descriptive approach.fThe theorymused in this research isvthe policy implementationmtheory of vanfMeter and vanmHorn which has sixrvariables that affectfperformance of public policydimplementation. The variables are policymstandarts and objectives; Themresources; The characteristics ofmimplementing agencies; The Comunicationmofkinter-organizational; The dispositionmor response of the implementers andmThe economic, socialmand political environment. Based onmthe results of the research,mthemimplementation of landmregistration policy throughmPTSL program in Tabanan Regency hasmbeenmrunning wellmbut not optimalmbecause theremare somemobstacles to the measurementmvariables includingmlack of humanmresources, poor communication inter-organizationsmand lack of publicmawarenessmin registering land. Keyword: Implementation,mPolicy, LandnRegistration